Occurrence and outcomes of retrobulbar haematoma in 2149 orbital fracture patients - Narjus-Sterba, Matilda; Puolakkainen, Tero; Kokko, Linda; Thoren, Hanna; Snäll, Johanna (Springer Science and Business Media LLC, 2025)
Purpose: We identified the occurrence of acute retrobulbar haematoma (RBH) across a complete range of orbital fractures and determined clinical and radiological findings that could predict permanent vision loss associated with RBH.
Methods: A retrospective analysis was conducted on data from facial trauma patients, encompassing a comprehensive range of orbital fractures. The primary outcome variable was the presence of acute RBH that required surgical or medical treatment. The main predictor variables were the types of orbital fractures. We collected data on symptoms, clinical and radiological findings, treatment, and instances of vision loss to assess the relationship between these factors and vision impairment.
Results: Of the 2149 patients with orbital fractures, 28 (1.3%) presented with acute RBH, including two bilateral haematomas, bringing the total number of RBHs to 30. Specific injury mechanisms were statistically associated with RBH (p = 0.005), with high-energy injuries being the most frequent cause. The prevalence of RBH was higher in bilateral than unilateral fractures (3.1% vs. 1.1%) (p = 0.023). Among unilateral fractures, RBH was most strongly linked to orbital roof and rim fractures. Tenting or tuliped-like appearance on computed tomography and absence of pupillary light reflex were more common in patients with permanent vision loss. Type of surgical approach did not affect visual outcome.
Conclusion: Acute RBH appears to occur more frequently in patients with orbital fractures than previously reported. Clinicians managing facial fractures need to be trained to diagnose RBH promptly and identify indicators of potential vision loss, particularly tenting on radiological images and changes in pupillary reflex.